Solea senegalensis Bacterial Intestinal Microbiota Is Affected by Low Dietary Inclusion of Ulva ohnoi - Cerezo, Isabel M.; Fumanal, Milena; Tapia-Paniagua, Silvana T.; Bautista, Rocio; Anguís, Victoria; Fernández-Díaz, Catalina; Alarcón, Francisco Javier; Moriñigo, Miguel A.; Balebona, M. Carmen (Frontiers in Microbiology, 2022)
The inclusion of macroalgae in the diets of farmed fish offers the opportunity for an added-value dietary ingredient to the nutraceutical feed. The composition of algae varies greatly among species. Several Ulva species have been considered in aquafeed formulations for different farmed fish, and Ulva ohnoi is being applied recently. However, the effects of seaweed dietary inclusion on the host must be evaluated. Considering the important role of the host intestinal microbiota, the potential effects of U. ohnoi dietary inclusion need to be studied. In this study, the characterization of the intestinal microbiome of Solea senegalensis, a flatfish with high potential for aquaculture in South Europe, receiving U. ohnoi (5%) supplemented diet for 90 d has been carried out. In addition, the functional profiles of bacterial communities have been determined by using PICRUSt, a computational approach to predict the functional composition of a metagenome by using marker gene data and a database of reference genomes. The results show that long-term dietary administration of U. ohnoi (5%)-supplemented feed modulates S. senegalensis intestinal microbiota, especially in posterior intestinal section. Increased relative abundance of Vibrio jointly with decreased Stenotrophomonas genus has been detected in fish receiving Ulva diet compared to control-fed fish. The influence of the diet on the intestinal functionality of S. senegalensis has been studied for the first time. Changes in bacterial composition were accompanied by differences in predicted microbiota functionality. Increased abundance of predicted genes involved in xenobiotic biodegradation and metabolism were observed in the microbiota when U. ohnoi diet was used. On the contrary, predicted percentages of genes associated to penicillin and cephalosporin biosynthesis as well as beta-lactam resistance were reduced after feeding with Ulva diet.